Design, Development and Expert Evaluation of the MARHIME Prototype for HI Museum Visitors’ Engagement - Esraa Jaffar Baker, Juliana Aida Abu Bakar, Abdul Nasir Zulkifli, Ruzinoor Che Mat, Mohd Fitri Yusoff, Mazida Ahmad, Azizah Che Omar (International Journal of Advanced Science and Technology, 2020)
The smartphones provide easy access to experience Augmented Reality (AR). Mobile Augmented Reality (MAR) technology is adopted to enhance human’s perception and help them to see, feel, and hear the environments in new and enhanced ways. Researchers have growing interest in the MAR environment to enhance museum visitors’ experiences in engagement, enjoyment, learning and personalized manners. Most of the museum MAR apps are designed for normal hearing people. While the hearing-impaired (HI) visitors are less fortunate. Thus, the HI visitors have to go through unpleasant experiences and ultimately become dissatisfied with their museum visit. This paper discusses on the process of design, development and expert evaluation of the Mobile Augmented Reality for hearing impaired museum visitors’ engagement (MARHIME) prototype. The goal of this prototype is to engage the HI museum visitors through the AR contents designed that replace their lost or missing hearing senses. The MARHIME prototype’s design has gone through several refining and evaluation sessions based on the predetermined objectives. The prototype has the necessary features to realize these objectives. The prototype has been designed and developed specifically for the Iraq museum which was specifically chosen since it has some of the most famous and historical artifacts in the world.